Preliminary studies on agonistic behavior between colonies of Coptotermes havilandi (Isoptera, Rhinotermitidae) in laboratory bioassays - Costa-Leonardo, Ana Maria [UNESP]; De Camargo-Dietrich, Célia Regina R. [UNESP]; Arab, Alberto [UNESP] (My University, 2002)
Intercolonial aggression is being used to delimit foraging territory in termite species of subterranean termites. The advance of the introduced pest termite Coptotermes havilandi Holmgren in the interior of São Paulo State is increasing its economic impact as well as its interspecific and intraspecific competition in Brazil. In order to evaluate the intraspecific agonism among different colonies collected in urban areas of Sȧo Paulo State were set up a series of preliminary bioassays. Different combination of nestmates from field colonies of C. havilandi of Rio Claro city showed lack of agonistic behavior. Nevertheless, encounters among individuals from São Paulo and Rio Claro cities showed agonistic behaviors. These preliminary results suggest that caution should be taken in using intercolonial aggression to delimit the foraging territory of C. havilandi colonies in São Paulo State.
Keywords: Agonistic behavior; Coptotermes; Intraspecific competition; Isoptera; Nestmate recognition; Subterranean termites; Coptotermes havilandi